Successive Differentiation in Calculus

Successive differentiation helps find higher-order derivatives, essential in mechanics, motion analysis, and differential equations.

Neetesh Kumar

Neetesh Kumar | February 08, 2025                                      \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space \space Share this Page on: Reddit icon Discord icon Email icon WhatsApp icon Telegram icon


Table of Content:


Definition of Successive Differentiation:

Successive Differentiation:
Successive differentiation is the process of differentiating a function more than once, i.e., computing the first, second, third, and higher order derivatives of a function.

For example, if f(x)f(x) is a differentiable function, then the first derivative is f(x)f'(x), the second derivative is f(x)f''(x), the third derivative is f(3)(x)f^{(3)}(x), and so on.

The n-th derivative of a function is denoted as:

f(n)(x)=dndxn(f(x))f^{(n)}(x) = \dfrac{d^n}{dx^n} \bigg(f(x)\bigg)


Formula Used:

  • First derivative: f(x)=ddx(f(x))f'(x) = \dfrac{d}{dx} (f(x))
  • Second derivative: f(x)=d2dx2(f(x))f''(x) = \dfrac{d^2}{dx^2} (f(x))
  • Third derivative: f(3)(x)=d3dx3(f(x))f^{(3)}(x) = \dfrac{d^3}{dx^3} (f(x))
    \cdot \cdot \cdot \cdot \cdot \cdot \cdot
  • n-th derivative: f(n)(x)=dndxn(f(x))f^{(n)}(x) = \dfrac{d^n}{dx^n} (f(x))

The process is simple: we keep differentiating the function until we obtain the desired derivative order. For example, the second derivative is the derivative of the first derivative, and the third derivative is the derivative of the second, and so on.


Derivative Examples with Solutions:

Example 1: Differentiating a Polynomial Function

Differentiate f(x)=3x45x3+2x27x+1f(x) = 3x^4 - 5x^3 + 2x^2 - 7x + 1 and find the second and third derivatives.

Solution:

First, find the first derivative:

f(x)=ddx(3x45x3+2x27x+1)f'(x) = \dfrac{d}{dx} (3x^4 - 5x^3 + 2x^2 - 7x + 1)

f(x)=12x315x2+4x7f'(x) = 12x^3 - 15x^2 + 4x - 7

Now, find the second derivative:

f(x)=ddx(12x315x2+4x7)f''(x) = \dfrac{d}{dx} (12x^3 - 15x^2 + 4x - 7)

f(x)=36x230x+4f''(x) = 36x^2 - 30x + 4

Finally, find the third derivative:

f(3)(x)=ddx(36x230x+4)f^{(3)}(x) = \dfrac{d}{dx} (36x^2 - 30x + 4)

f(3)(x)=72x30f^{(3)}(x) = 72x - 30

Thus, the derivatives are:

  • First derivative: f(x)=12x315x2+4x7f'(x) = 12x^3 - 15x^2 + 4x - 7
  • Second derivative: f(x)=36x230x+4f''(x) = 36x^2 - 30x + 4
  • Third derivative: f(3)(x)=72x30f^{(3)}(x) = 72x - 30

Example 2: Differentiating a Trigonometric Function

Differentiate f(x)=sin(x2)f(x) = \sin(x^2) and find the first and second derivatives.

Solution:

First, apply the chain rule to find the first derivative:

f(x)=ddxsin(x2)f'(x) = \dfrac{d}{dx} \sin(x^2)

f(x)=2xcos(x2)f'(x) = 2x \cos(x^2)

Now, find the second derivative:

f(x)=ddx(2xcos(x2))f''(x) = \dfrac{d}{dx} (2x \cos(x^2))

Using the product rule, we get:

f(x)=2cos(x2)4x2sin(x2)f''(x) = 2\cos(x^2) - 4x^2 \sin(x^2)

Thus, the derivatives are:

  • First derivative: f(x)=2xcos(x2)f'(x) = 2x \cos(x^2)
  • Second derivative: f(x)=2cos(x2)4x2sin(x2)f''(x) = 2\cos(x^2) - 4x^2 \sin(x^2)

Example 3: Differentiating a Logarithmic Function

Differentiate f(x)=ln(x2+1)f(x) = \ln(x^2 + 1) and find the second derivative.

Solution:

First, find the first derivative using the chain rule:

f(x)=ddxln(x2+1)f'(x) = \dfrac{d}{dx} \ln(x^2 + 1)

f(x)=2xx2+1f'(x) = \dfrac{2x}{x^2 + 1}

Now, find the second derivative:

f(x)=ddx(2xx2+1)f''(x) = \dfrac{d}{dx} \left( \frac{2x}{x^2 + 1} \right)

Using the quotient rule:

f(x)=(x2+1)(2)(2x)(2x)(x2+1)2f''(x) = \dfrac{(x^2 + 1)(2) - (2x)(2x)}{(x^2 + 1)^2}

f(x)=2(x2+1)4x2(x2+1)2f''(x) = \dfrac{2(x^2 + 1) - 4x^2}{(x^2 + 1)^2}

f(x)=22x2(x2+1)2f''(x) = \dfrac{2 - 2x^2}{(x^2 + 1)^2}

Thus, the derivatives are:

  • First derivative: f(x)=2xx2+1f'(x) = \dfrac{2x}{x^2 + 1}
  • Second derivative: f(x)=22x2(x2+1)2f''(x) = \dfrac{2 - 2x^2}{(x^2 + 1)^2}

Example 4: Differentiating an Exponential Function

Differentiate f(x)=e3x2+2xf(x) = e^{3x^2 + 2x} and find the first and second derivatives.

Solution:

First, find the first derivative using the chain rule:

f(x)=ddxe3x2+2xf'(x) = \dfrac{d}{dx} e^{3x^2 + 2x}

f(x)=e3x2+2x(6x+2)f'(x) = e^{3x^2 + 2x} \cdot (6x + 2)

Now, find the second derivative:

f(x)=ddx(e3x2+2x(6x+2))f''(x) = \dfrac{d}{dx} \left( e^{3x^2 + 2x} (6x + 2) \right)

Using the product rule:

f(x)=e3x2+2x(6x+2)2+e3x2+2x6f''(x) = e^{3x^2 + 2x} \cdot (6x + 2)^2 + e^{3x^2 + 2x} \cdot 6

f(x)=e3x2+2x((6x+2)2+6)f''(x) = e^{3x^2 + 2x} \left( (6x + 2)^2 + 6 \right)

Thus, the derivatives are:

  • First derivative: f(x)=e3x2+2x(6x+2)f'(x) = e^{3x^2 + 2x} (6x + 2)
  • Second derivative: f(x)=e3x2+2x((6x+2)2+6)f''(x) = e^{3x^2 + 2x} \left( (6x + 2)^2 + 6 \right)

Conclusion:

  • Successive differentiation allows us to calculate higher-order derivatives of a function, useful in many fields like physics (acceleration, jerk), economics, and engineering.
  • Higher derivatives provide insights into the behavior of functions, such as curvature and rates of change.
  • This concept is fundamental in optimization problems, motion analysis, and curve sketching.